RESPONS PAKCOY TERHADAP APLIKASI PUPUK ORGANIK CAIR PGPR PADA SISTEM HIDROPONIK WICK - Sri Sudewi; Hasmari Noer; Abdul Rahim Saleh (AGRICA, 2026)
This study was conducted to assess the effectiveness of PGPR-based liquid organic fertiliser as a partial substitute for AB Mix nutrients, and to determine the optimal composition of AB Mix and POC PGPR for supporting pakcoy growth and yield in a wick hydroponic system using recycled bottles. This study used a non-factorial Randomised Block Design (RBD) with seven treatments repeated four times. The treatments included a control without nutrients (P0), 100% AB Mix (P1), 75% AB Mix + 25% PGPR (P2), 50% AB Mix + 50% PGPR (P3), 25% AB Mix + 75% PGPR (P4), PGPR 100% (P5), and POC Jakaba 100% (P6). The variables observed included plant height, number of leaves, and fresh weight of roots and shoots. The results showed that the AB Mix 75% + POC PGPR 25% (P2) formulation provided the best growth response in terms of plant height (21.53 cm), number of leaves (9.33 leaves), and fresh canopy weight (17.18 g) at 28 HSPT, and was not significantly different from AB Mix 100% (P1). Meanwhile, treatments without inorganic nutrients (P1 and P6) showed lower growth, confirming that without adequate inorganic nutrient support, plant growth response is limited. The AB Mix 75% + POC PGPR 25% formulation is a treatment combination that has the potential to reduce synthetic fertilizer use by utilizing locally sourced, microbial-based POC as part of more sustainable agricultural practices.